STFU : the power of keeping your mouth shut in an endlessly noisy world - Lyons, Daniel, 1960- (Henry Holt and Company, 2023)
"A desperately needed wake-up call for a world that demands we keep tweeting, posting, and podcasting that proves the most important thing might be to shut up! By identifying the six types of overtalkers and the six principles to cure our babbling ways, STFU empowers us to become better at nearly every facet of our daily lives and in our most treasured relationships"--